Quality Of Work Life Of Nurse Anesthetist During Covid-19 In Indonesia - Richa Noprianty; Fikri Mourly (Universitas Muhammadiyah Yogyakarta, 2021)
Nurse anesthetist are health workers who are competent to carry out anesthetic administration care in hospitals. The quality of the anesthetic administration care provided reflects the quality of the hospital. Anesthesiologists in carrying out their competence are in a work setting with high stressors. Therefore, it is necessary to pay attention to the Quality of Work Life in the anesthesiologist. The purpose of this study was to photograph the Quality of Work Life of anesthesiologists in a hospital. This study uses a quantitative descriptive method. The study population was all anesthesiologists working in the hospital. The research sample used simple random sampling method with a total of 108 respondents. The instrument used is a questionnaire that is given online using four dimensions, namely the dimensions of life at work/home, the dimensions of work design, the dimensions of the work context and the dimensions of the world of work. The analysis used is univariate using a mean value of 105. Data collection using gform, The results obtained are the mean value of 124.28. For each dimension, the dimensions of life at work/home are 20.03, the work design dimension is 29.08, the context dimension is 61.70, and the world of work is 13.46. The conclusion is that the Quality of Work Life of the anesthesiologist in the hospital is in the good category. Suggested in this study is the development of human resources that lead to a high workload and a great risk of anesthesia